Composition, mixture for electrochemical device, mixture sheet for electrochemical device, electrochemical device, and method for manufacturing mixture sheet for electrochemical device

JP2025036344APending Publication Date: 2025-03-14DAIKIN INDUSTRIES LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024147731
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0024】 本開示によれば、硫化物固体電解質を有する電気化学デバイスの抵抗を低減できる組成物、電気化学デバイス用合剤、電気化学デバイス用合剤シート、電気化学デバイス、及び、電気化学デバイス用合剤シートの製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036344000001
    Figure 2025036344000001
  • Figure 2025036344000002
    Figure 2025036344000002
  • Figure 2025036344000003
    Figure 2025036344000003
Patent Text Reader

Abstract

To provide a composition which can reduce resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for an electrochemical device, a mixture sheet for an electrochemical device, an electrochemical device, and a method for manufacturing a mixture sheet for an electrochemical device.SOLUTION: A composition contains a sulfide solid electrolyte, fluoropolyether, and a fibrillable resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composition, a mixture for electrochemical devices, a mixture sheet for electrochemical devices, an electrochemical device, and a method for producing a mixture sheet for electrochemical devices. [Background technology]

[0002] 2. Description of the Related Art With the trend toward lighter and smaller electric appliances in recent years, the development of electrochemical devices having high energy density, such as lithium ion secondary batteries, has progressed.

[0003] As technologies relating to electrochemical devices, Patent Document 1 discloses a solid electrolyte composition containing a specific (per)fluoropolyether, a specific poly(alkylene) oxide, and a lithium salt, and Patent Document 2 discloses a solid electrolyte slurry containing an inorganic solid electrolyte material, and a liquid such as perfluoropolyether and silicone oil, and in which the content of a binder resin is adjusted to a specific range. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2022-506854 [Patent Document 2] JP 2016-062709 A Summary of the Invention [Problem to be solved by the invention]

[0005] When manufacturing an electrochemical device such as a secondary battery, it is believed that the resistance of the electrodes and the like is reduced by pressing the electrodes and the like at high pressure. In particular, when manufacturing an electrochemical device having a sulfide solid electrolyte, it is believed that the effect of reducing the resistance by high pressure pressing is remarkable. On the other hand, in order to simplify the manufacturing process of the electrochemical device and reduce the manufacturing cost, it is required to press the electrodes and the like at low pressure. However, when a low pressure press is used in manufacturing an electrochemical device having a sulfide solid electrolyte, the above-mentioned effect of reducing the resistance tends to be difficult to obtain. Therefore, a new technology is needed to reduce the resistance of an electrochemical device having a sulfide solid electrolyte.

[0006] An object of the present disclosure is to solve the above-mentioned problems and to provide a composition capable of reducing the resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for electrochemical devices, a mixture sheet for electrochemical devices, an electrochemical device, and a method for producing a mixture sheet for electrochemical devices. [Means for solving the problem]

[0007] The present disclosure (1) is a composition comprising a sulfide solid electrolyte, a fluoropolyether and a fibrillating resin.

[0008] The present disclosure (2) is the composition according to the present disclosure (1), wherein the fluoropolyether is at least one of the following formulas (1) to (4). (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R4 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0009] This disclosure (3) relates to the Ra 1 ~Ra 3 are each independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH2CH2O)r-(CH2CH(CH3)O)s-(CH2CH(CH2CH3)O)t-(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0010] The present disclosure (4) relates to the Ra 1 ~Ra 3 The composition according to the present disclosure (2) or (3), wherein the number average molecular weight is 40 to 4,000.

[0011] The present disclosure (5) is the composition according to any one of the present disclosures (2) to (4), in which the Rfs are each independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3Rc6)d-(OC2F4)e-(OCF2)f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0012] The present disclosure (6) is the composition according to any one of the present disclosures (2) to (5), in which the Rfs are each independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary.

[0013] This disclosure (7) relates to the R 1 ~R 3 is the composition according to any one of the present disclosures (2) to (6), wherein each of

[0014] The present disclosure (8) is the composition according to any one of the present disclosures (1) to (7), wherein the fibrillary resin is polytetrafluoroethylene.

[0015] The present disclosure (9) is the composition according to any one of the present disclosures (1) to (8), wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

[0016] The present disclosure (10) is the composition according to any one of the present disclosures (1) to (9), in which the content of the polyalkylene oxide represented by the following formula (6) is less than 20 mass %. (6)R 1B -(OCHR 1A (CH2)jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0017] The present disclosure (11) is the composition according to any one of the present disclosures (1) to (10), wherein the content of the lithium salt relative to the fluoropolyether is 0.1 to 30% by mass.

[0018] The present disclosure (12) is a mixture for electrochemical devices, comprising the composition according to any one of the present disclosures (1) to (11).

[0019] The present disclosure (13) is a mixture for electrochemical devices according to the present disclosure (12), which contains a conductive assistant.

[0020] The present disclosure (14) is a mixture sheet for electrochemical devices, comprising the mixture for electrochemical devices according to the present disclosure (12) or (13).

[0021] The present disclosure (15) is an electrochemical device using the mixture sheet for electrochemical devices according to the present disclosure (14).

[0022] The present disclosure (16) provides a process for producing a fluoropolyether-based electrochemical device, comprising the steps of: (1) mixing a fluoropolyether, a fibrillar resin, and a sulfide solid electrolyte; and (2) rolling the composition obtained in the step (1) into a sheet.

[0023] The present disclosure (17) relates to a fluoropolyether having at least one of the following formulas (1) to (4): This is the manufacturing method according to the present disclosure (16), wherein the fibrillar resin is polytetrafluoroethylene. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II). Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Effect of the Invention

[0024] Effects of the Invention According to the present disclosure, it is possible to provide a composition capable of reducing the resistance of an electrochemical device having a sulfide solid electrolyte, a mixture for electrochemical devices, a mixture sheet for electrochemical devices, an electrochemical device, and a method for producing a mixture sheet for electrochemical devices. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present disclosure will now be described in detail.

[0026] <Composition> The present disclosure relates to a composition comprising a sulfide solid electrolyte, a fluoropolyether and a fibrillating resin.

[0027] Since the composition of the present disclosure has the above-mentioned configuration, it is possible to reduce the resistance of an electrochemical device having a sulfide solid electrolyte.

[0028] The sulfide solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(x=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S.6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12 , LiI-LiBr-Li2S-P2S5, etc., or a mixture of two or more of them can be used. Among them, LiI-LiBr-Li2S-P2S5 is particularly preferred.

[0029] The sulfide solid electrolyte preferably contains lithium. The sulfide solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0030] In the composition of the present disclosure, the content of the sulfide solid electrolyte is preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more, and is preferably 99.9 mass % or less.

[0031] As the fluoropolyether, at least one of the following formulae (1) to (4) can be suitably used. These compounds include Rb 1 ~Rb 4 The portion exhibits good lubricity and reduces grain boundary resistance. 1 ~Ra 3 Since ionic conductivity is imparted by the portion, the grain boundary resistance can be further reduced. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (4)R4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 each oxyalkylene unit is independently -CHCHO- or -CHCH(J)O-; Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0032] Ra 1 ~Ra 3 The alkylene unit may be linear or branched, but is preferably linear, and preferably has 1 to 3 carbon atoms.

[0033] Ra 1 ~Ra 3When the oxyalkylene unit is -CHCH(J)O-, the alkyl group of J may be linear or branched, but is preferably linear. The number of carbon atoms in the alkyl group of J is preferably 1 to 3. Examples of the aryl group represented by J include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0034] Ra 1 ~Ra 3 In the formula (I), the number of fluorine-free alkylene units and fluorine-free oxyalkylene units is preferably 4 to 50 in total.

[0035] Ra 1 ~Ra 3 Each of the groups preferably independently contains at least an oxyalkylene unit, and is more preferably a polyoxyalkylene group represented by the following formula (Ra-I). (Ra-I): -(CH2CH2O)r-(CH2CH(CH3)O)s-(CH2CH(CH2CH3)O)t-(CH2CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0036] In the above formula (Ra-I), r is preferably 1 or more, more preferably 2 or more, and is preferably 30 or less, more preferably 20 or less. s, t and u are preferably 10 or less, more preferably 5 or less, and further preferably 0. r+s+t+u is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.

[0037] Ra 1 ~Ra 3 The number average molecular weight of is preferably 40 or more, more preferably 100 or more, and is preferably 4000 or less, more preferably 1000 or less. In the present specification, Ra 1 ~Ra 3 The number average molecular weight of 1 This is a value measured by H-NMR.

[0038] Rb 1 ~Rb 4 In the above formula (5), Rf 1 and Rf 2 The alkylene group may be linear or branched, but is preferably linear. Rf 1 and Rf 2 The alkylene group is preferably a fluorine-substituted alkylene group substituted with a fluorine atom. Rf 1 and Rf 2 The alkylene group preferably has 1 to 3 carbon atoms.

[0039] Rb 1 ~Rb 4 In the above formula (5), Rf may have a ring structure.

[0040] Rb 1 ~Rb 4 In the above formula (5), Rf is preferably a fluoropolyether group represented by the following formula (Rf-I). Formula (Rf-I): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3Rc6)d-(OC2F4)e-(OCF2)f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0041] Rc is preferably a hydrogen atom or a fluorine atom, and more preferably a fluorine atom, That is, Rf in the formula (5) is preferably a perfluoropolyether group.

[0042] It is preferable that a, b, c, d, e and f each independently represent an integer of 0 to 100.

[0043] The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more or 20 or more. The sum of a, b, c, d, e and f is preferably 100 or less, more preferably 60 or less, and may be 50 or less or 30 or less.

[0044] Each repeat unit denoted by a, b, c, d, e, or f may be linear or branched. -(OC6F 12 )- may be, for example, any of -(OCF2CF2CF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2CF2CF2)-, -(OCF2CF(CF3)CF2CF2CF2)-, -(OCF2CF2CF(CF3)CF2CF2)-, -(OCF2CF2CF2CF(CF3)CF2)-, or -(OCF2CF2CF2CF2CF(CF3))-. -(OC5F 10 )- may be, for example, any of -(OCF2CF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2CF2)-, -(OCF2CF(CF3)CF2CF2)-, -(OCF2CF2CF(CF3)CF2)-, or -(OCF2CF2CF2CF(CF3))-. -(OC4F8)- may be, for example, any of -(OCF2CF2CF2CF2)-, -(OCF(CF3)CF2CF2)-, -(OCF2CF(CF3)CF2)-, -(OCF2CF2CF(CF3))-, -(OC(CF3)2CF2)-, -(OCF2C(CF3)2)-, -(OCF(CF3)CF(CF3))-, -(OCF(C2F5)CF2)-, or -(OCF2CF(C2F5))-. -(OC3F6)- (that is, in the above formula (Rf-I) where all Rc are fluorine atoms) may be, for example, any of -(OCF2CF2CF2)-, -(OCF(CF3)CF2)-, and -(OCF2CF(CF3))-. -(OC2F4)- may be, for example, -(OCF2CF2)- or -(OCF(CF3))-.

[0045] Rf may be a group represented by any one of the following formulas (Rf-II) to (Rf-IV). Formula (Rf-II): -(OC3F6)d-(OC2F4)e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Formula (Rf-I-III): -(R 20 -R 21 )g- (In the formula, R 20 is OCF2 or OC2F4, R 21 are OC2F4, OC3F6, OC4F8, OC5F 10 and OC6F 12 or a combination of two or three groups selected from these groups, g is an integer from 2 to 100. Formula (Rf-I-IV): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, e is an integer of 1 to 200, a, b, c, d, and f each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. Formula (Rf-IV): -(OC6F 12 )a-(OC5F 10 )b-(OC4F8)c-(OC3F6)d-(OC2F4)e-(OCF2)f- (In the formula, f is an integer of 1 to 200, a, b, c, d, and e each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary.

[0046] In the above formula (Rf-II), d may be preferably 5-200, more preferably 10-100, and further preferably 10-30. The above formula (Rf-II) is preferably a group represented by -(OCF2CF2CF2)d- or -(OCF(CF3)CF2)d-.

[0047] In the above formula (Rf-I-II), e and f are each independently an integer of preferably 5 to 200, more preferably 10 to 200. The sum of c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more, or 20 or more. The above formula (Rf-I-II) is preferably a group represented by -(OCF2CF2CF2CF2)c-(OCF2CF2CF2)d-(OCF2CF2)e-(OCF2)f- or a group represented by -(OC2F4)e-(OCF2)f-, and more preferably a group represented by -(OC2F4)e-(OCF2)f-.

[0048] In the above formula (Rf-I-III), R 20 is preferably OC2F4, and R 21is preferably a group selected from OC2F4, OC3F6 and OC4F8, or a combination of two or three groups independently selected from these groups, and more preferably a group selected from OC3F6 and OC4F8. The combination of two or three groups independently selected from OC2F4, OC3F6 and OC4F8 is not particularly limited, and examples thereof include -OC2F4OC3F6-, -OC2F4OC4F8-, -OC3F6OC2F4-, -OC3F6OC3F6-, -OC3F6OC4F8-, -OC4F8OC4F8-, -OC4F8OC3F6-, -OC4F8OC2F4-, -OC Examples include 2F4OC2F4OC3F6-, -OC2F4OC2F4OC4F8-, -OC2F4OC3F6OC2F4-, -OC2F4OC3F6OC3F6-, -OC2F4OC4F8OC2F4-, -OC3F6OC2F4OC2F4-, -OC3F6OC2F4OC3F6-, -OC3F6OC3F6OC2F4-, and -OC4F8OC2F4OC2F4-. In the above formula (Rf-I-III), g is preferably an integer of 3 or more, more preferably an integer of 5 or more. The above g is preferably an integer of 50 or less. In the above formula (Rf-I-III), OC2F4, OC3F6, OC4F8, OC5F 10 , and OC6F 12 may be either linear or branched, and is preferably linear. In this embodiment, the above formula (Rf-I-III) is preferably -(OC2F4-OC3F6)g- or -(OC2F4-OC4F8)g-.

[0049] In the above formula (Rf-I-IV), e is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0050] In the above formula (Rf-IV), f is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0051] In Rf, the ratio of e to f (hereinafter referred to as "e / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the e / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the e / f ratio, the more the lubricity is improved. On the other hand, by making the e / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the e / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the e / f ratio is preferably 0.8 or more.

[0052] Rf is represented by the following formula (Rf-I-VI): -(OCF2CF2CF2)a-(OCF(CF3)CF2)b-(OCF2CF(CF3))c-(OCF2CF2)d-(OCF(CF3))e-(OCF2)f- (In the formula, a, b, c, d, e, and f each independently represent an integer of 0 to 200, the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. The group may be represented by the following formula:

[0053] Rf is represented by the following formula (Rf-I-VII): -(OCF2CF2)d-(OCF(CF3))e-(OCF2)f- (In the formula, d, e, and f each independently represent an integer of 0 to 200, the sum of d, e, and f is 1 or more, The order of the repeating units marked with d, e, or f is arbitrary. When Rf is this group, it is considered that the solubility of the salt is improved since the number of ether bonds increases and the cations of the salt are more easily coordinated.

[0054] In Rf, the ratio of d to f (hereinafter referred to as "d / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the d / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the d / f ratio, the more the lubricity is improved. On the other hand, by making the d / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the d / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the d / f ratio is preferably 0.8 or more.

[0055] Each Rf is preferably independently a group represented by the above formula (Rf-II) or the above formula (Rf-I-II), and more preferably a group represented by the above formula (Rf-I-II).

[0056] The number average molecular weight of Rf is not particularly limited, but is, for example, 500 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. In this specification, the number average molecular weight of Rf is 19 This is a value measured by F-NMR.

[0057] R 1 ~R 3 The alkyl group and the fluoroalkyl group may be linear or branched, but are preferably linear. R 1 ~R 3 Examples of the aryl group include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0058] R 1 ~R 3are each independently preferably an alkyl group having 1 to 3 carbon atoms or a fluoroalkyl group having 1 to 3 carbon atoms, more preferably a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group, and further preferably a methyl group, a trifluoromethyl group or a pentafluoroethyl group.

[0059] R 4 The alkyl ester group may be linear or branched.

[0060] R 4 Examples of the substituent that the amido group or amino group may have include an alkyl group, an alkoxy group, and a hydroxy group.

[0061] R 4 are each preferably independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent, and more preferably a fluorine atom. R 4 is a fluorine atom, R 4 -Rb 4 and Rb 4 -R 4 , i.e., R 4 -Rf 1 and Rf 2 -R 4 may each independently be a group selected from the group consisting of -CF3, -CF2CF3, and -CF2CF2CF3.

[0062] The fluoropolyether is preferably at least one selected from the group consisting of the formula (1) and the formula (4), and particularly preferably the formula (1), because it has good ionic conductivity and the like.

[0063] The above-mentioned fluoropolyether is preferably liquid at any temperature between 25°C and 80°C, and more preferably liquid at 25°C, because it has good ionic conductivity and the like. Examples of a form that is "liquid at any temperature between 25°C and 80°C" include a form that is solid at 25°C and liquid at 50°C, and a form that is solid at 50°C and liquid at 80°C. A form that is liquid at low temperatures and solid at high temperatures does not usually exist, and therefore is not included in the form that is "liquid at any temperature between 25°C and 80°C".

[0064] In the composition of the present disclosure, the content of the fluoropolyether is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more, based on the solid material, and is preferably 25 mass% or less, more preferably 15 mass% or less, and even more preferably 10 mass% or less. The solid material is a material to which the lubricating function is imparted by the fluoropolyether, and is solid after mixing with the fluoropolyether. The solid material does not include substances (such as lithium salts) that dissolve in the fluoropolyether after mixing. In the examples described below, the positive electrode active material, solid electrolyte, conductive assistant, and binder (fibrillar resin) correspond to the solid material.

[0065] The fibrillary resin is a resin that easily fibrillates when a shear stress is applied, and examples thereof include liquid crystal polymer (LCP), cellulose, acrylic resin, ultra-high molecular weight polyethylene, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more. Among them, PTFE is preferred from the viewpoints of chemical stability, thermal stability, and processability.

[0066] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. As the PTFE, the modified PTFE is preferred in that it improves the binding force, sheet strength and flexibility.

[0067] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving the binding force, sheet strength, and flexibility. The lower limit of the modified monomer unit content is preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and even more preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, and even more preferably 0.30% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0068] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0069] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0070] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORff (A) (wherein Rff represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0071] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rff in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0072] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0073] The perfluorovinyl ether further includes those in which, in the above general formula (A), Rff is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rff is the following formula:

[0074] [ka]

[0075] (wherein m represents 0 or an integer of 1 to 4), Rff is a group represented by the following formula:

[0076] [ka]

[0077] (wherein n represents an integer of 1 to 4).

[0078] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0079] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORff 1 (B) (In the formula, Rff 1 represents a perfluoro organic group.

[0080] Rff 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.

[0081] As the modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the composite sheet, at least one selected from the group consisting of PAVE, HFP, VDF, and CTFE is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) [PMVE], HFP, VDF, and CTFE is more preferable.

[0082] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0083] Examples of PTFE that are commonly available on the market include F-104, F-106, F-107, F-104C, F-121, F-201, F-205, F-208, and F-302 manufactured by Daikin Industries, 60X, 601X, 602X, 605XTX, 613AX, 62X, 62NX, 62XTX, 640XTX, 641XTX, 650XTX, 669X, 669NX, 6CX, 6CNX, CFP6000X, 6J, 6CJ, 62J, 640J, and 641J manufactured by Chemours, and T manufactured by 3M. F2029, TF2025Z, TF2053Z, TF2073Z, TF2001Z, TF2071USZ, TF2072Z, etc., CD145, CD123, CD126E, CD097, CD084E, CD086EL, CD086EH, CD090E, CD122E, CD141E, CD127E, etc., manufactured by AGC, and DF681F, DF680F, DF330F, DF291F, DF230F, DF210F, DF132F, DF130F, DF120F, etc., manufactured by Solvay.

[0084] In terms of being able to form a composite sheet having even greater strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0085] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0086] In the composition of the present disclosure, the content of the fibrillar resin, relative to the solid materials other than the fibrillar resin and other binders described below, is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, and is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less, and even more preferably 10 mass% or less.

[0087] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the following formula (6) is preferably less than 20% by mass. This ensures good ionic conductivity. If the content is 20% by mass or more, the viscosity of the composition increases, the ionic conductivity decreases, and the electrochemical stability tends to decrease. (6)R 1B -(OCHR 1A (CH2)jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0088] In the composition of the present disclosure, the content of the polyalkylene oxide represented by the above formula (6) is more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 1% by mass or less. The lower limit is not particularly limited, and may be 0% by mass.

[0089] The composition of the present disclosure may contain a lithium salt. By containing a lithium salt, the conductivity of lithium ions is improved.

[0090] Any lithium salt can be used as the lithium salt, and specific examples include the following: LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, LiWF7, LiAsF6, LiAlCl4, LiI, LiBr, LiCl, LiB 10 Cl 10 Inorganic lithium salts such as Li2SiF6, Li2PFO3, and LiPO2F2; Lithium tungstates such as LiWOF5; Lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; Lithium salts having an S=O group, such as FSO3Li, CH3SO3Li, CH2FSO3Li, CHF2SO3Li, CF3SO3Li, CF3CF2SO3Li, CF3CF2CF2SO3Li, CF3CF2CF2CF2SO3Li, lithium methyl sulfate, lithium ethyl sulfate (C2H5OSO3Li), and lithium 2,2,2-trifluoroethyl sulfate; Lithium imide salts such as lithium bis(trifluoromethanesulfonimide) (LiTFSI), lithium bis(monofluorosulfonimide) (LiFSI), LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium bisperfluoroethanesulfonylimide, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, lithium cyclic 1,2-ethanedisulfonylimide, lithium cyclic 1,3-propanedisulfonylimide, lithium cyclic 1,4-perfluorobutanedisulfonylimide, LiN(CF3SO2)(FSO2), LiN(CF3SO2)(C3F7SO2), LiN(CF3SO2)(C4F9SO2), and LiN(POF2)2; Lithium methide salts such as LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3; Others, Formula: LiPF a (C n F 2n+1 ) 6-a (wherein a is an integer of 0 to 5, and n is an integer of 1 to 6) (e.g., fluorine-containing organic lithium salts such as LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3F7)3, LiPF5(iso-C3F7), LiPF4(CF3)2, LiPF4(C2F5)2), LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2, LiSCN, LiB(CN)4, LiB(C6H5)4, Li2(C2O4), LiP(C2O4)3, Li2B 12 F b H 12-b (b is an integer of 0 to 3), etc.

[0091] Among these, LiTFSI, LiFSI, LiPF6, LiBF4, LiSbF6, LiTaF6, LiPO2F2, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, etc. are preferred, with LiTFSI, LiFSI, and LiPF6 being particularly preferred.

[0092] These lithium salts may be used alone or in combination of two or more. A preferred example of a combination of two or more is a combination of LiPF6 and LiBF4, or a combination of LiPF6 and LiPO2F2, C2H5OSO3Li or FSO3Li, which has the effect of improving high-temperature storage characteristics, load characteristics and cycle characteristics.

[0093] Another example is the combined use of an inorganic lithium salt and an organic lithium salt, which has the effect of suppressing deterioration due to high-temperature storage. As the organic lithium salt, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, etc. are preferred.

[0094] In the composition of the present disclosure, the content of the lithium salt relative to the fluoropolyether is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less.

[0095] <Compounds for electrochemical devices> INDUSTRIAL APPLICABILITY The composition of the present disclosure is capable of reducing the resistance of an electrochemical device and is therefore useful as a mixture for electrochemical devices. The present disclosure also relates to a mixture for an electrochemical device comprising the composition of the present disclosure.

[0096] In the mixture for electrochemical devices according to the present disclosure, the content of the composition according to the present disclosure is preferably 70 mass % or more, more preferably 80 mass % or more, even more preferably 90 mass % or more, and is preferably 99.9 mass % or less, more preferably 99.5 mass % or less, even more preferably 99 mass % or less.

[0097] The mixture for electrochemical devices according to the present disclosure may contain a conductive assistant. The conductive assistant is not particularly limited, but examples thereof include metal materials such as copper, nickel, and gold, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as vapor grown carbon fiber (VGCF). Among these, carbon materials are preferred, amorphous carbon is more preferred, and VGCF is even more preferred. These may be used alone or in any combination and ratio of two or more.

[0098] In the mixture for electrochemical devices of the present disclosure, the content of the conductive assistant is preferably 20 mass % or less, more preferably 15 mass % or less, and further preferably 10 mass % or less. The lower limit is not particularly limited, and may be 0 mass %.

[0099] In the mixture for electrochemical devices of the present disclosure, the fibrillar resin acts as a binder, but may further contain other binders. The other binders are not particularly limited, but examples thereof include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; EPDM (ethylene-propylene Examples of such polymers include thermoplastic elastomer-like polymers such as styrene-ethylene-butadiene terpolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, vinylidene fluoride copolymers, and tetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions). These may be used alone or in any combination and ratio of two or more.

[0100] In the mixture for electrochemical devices of the present disclosure, the content of the other binder is usually 0 to 10 mass % based on the solid materials other than the fibrillar resin and the other binder.

[0101] The mixture for electrochemical devices according to the present disclosure can be used as a solid electrolyte mixture. Moreover, by blending an electrode active material, it can also be used as an electrode mixture.

[0102] The electrode active material may be a positive electrode active material or a negative electrode active material.

[0103] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.

[0104] Examples of the alkali metal-containing transition metal composite oxide include: Formula: M a Mn 2-b M 1 b O4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), in which M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0105] Among these, MCoO2, MMnO2, MNiO2, MMn2O4, and MNi are the most popular because they can provide high energy density and high output secondary batteries. 0.8 Co 0.15 Al 0.05 O2 or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like are preferred, and a compound represented by the following general formula is preferred. MNi h Co i Mn j M 5 k O2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0106] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO4) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0107] The transition metal of the alkali metal-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. The lithium-containing transition metal phosphate compound is preferably one having an olivine structure.

[0108] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0109] Other positive electrode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 Fe 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3, etc. In particular, M2MnO3, MNi 0.5 Mn 1.5Positive electrode active materials such as O2 are preferable in that their crystal structures do not collapse even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or higher. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the positive electrode active material exemplified above is preferable because the remaining capacity hardly decreases, the resistance increase rate hardly changes, and the battery performance does not deteriorate even when operated at a high voltage, even when stored at a high temperature.

[0110] As other positive electrode active materials, solid solution materials such as M2MnO3 and MM 6 O2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) can also be mentioned.

[0111] Examples of the solid solution material include, for example, an alkali metal manganese oxide represented by the general formula M x [Mn (1-y) M 7 y O z Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and includes, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the range of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, a manganese-containing solid solution material in which LiNiO2 or LiCoO2 is solid-solved based on Li2MnO3 such as Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O2 is preferable in that it can provide an alkali metal ion secondary battery having a high energy density.

[0112] In addition, it is preferable to include lithium phosphate in the positive electrode active material, since the continuous charging characteristics are improved. Although there is no limitation on the use of lithium phosphate, it is preferable to use the positive electrode active material and lithium phosphate mixed together. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, with respect to the total of the positive electrode active material and lithium phosphate, and is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0113] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0114] The above positive electrode active materials may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Examples of such a combination include a combination with a ternary system such as O2, a combination of LiCoO2 and LiMn2O4 or a combination in which a portion of the Mn is replaced with another transition metal, or a combination of LiFePO4 and LiCoO2 or a combination in which a portion of the Co is replaced with another transition metal.

[0115] The content of the positive electrode active material is preferably 50 to 90% by mass of the positive electrode mixture in terms of high battery capacity. The content in the positive electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ion conductivity, electronic conductivity, and electrode strength may be insufficient.

[0116] The negative electrode active material is not particularly limited, and examples thereof include those containing carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; Li4Ti5O 12 The examples of the material include any one selected from the above, or a mixture of two or more of them. Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0117] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0118] The silicon-containing material includes silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, and silicon-based compounds having the general formula SiO x Silicon oxide particles represented by the formula (0.5≦x≦1.6) or a mixture thereof are preferred. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a higher capacity, and excellent cycle characteristics can be obtained.

[0119] In the present disclosure, silicon oxide is a general term for amorphous silicon oxide. Silicon oxide before disproportionation has the general formula SiO x(0.5≦x≦1.6). Preferably, x satisfies 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, and then cooling and precipitating the gas.

[0120] The content of the negative electrode active material is preferably 50 to 90% by mass of the negative electrode mixture in terms of high battery capacity. The content in the negative electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the negative electrode active material in the negative electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ionic conductivity, electronic conductivity, and electrode strength may be insufficient.

[0121] <Compound sheet for electrochemical devices> The mixture for electrochemical devices of the present disclosure is preferably in the form of a sheet. The present disclosure also relates to a mixture sheet for electrochemical devices, comprising the mixture for electrochemical devices of the present disclosure.

[0122] The thickness of the composite sheet for electrochemical devices of the present disclosure is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, and particularly preferably 150 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0123] The mixture sheet for electrochemical devices according to the present disclosure can be used as a solid electrolyte mixture sheet or an electrode mixture sheet.

[0124] <Method of manufacturing a composite sheet for electrochemical devices> The composite sheet for electrochemical devices of the present disclosure can be obtained, for example, by a production method including a step (1) of mixing a fluoropolyether, a fibrillar resin, and a sulfide solid electrolyte, and a step (2) of rolling the composition obtained in the step (1) into a sheet. The present disclosure also relates to such a method of manufacture.

[0125] The fluoropolyether, fibrillating resin, and sulfide solid electrolyte in the above step (1) are the same as those described in the composition of the present disclosure.

[0126] In the above step (1), the mixing conditions are preferably 3000 rpm or less. The speed is preferably 10 rpm or more, more preferably 15 rpm or more, and even more preferably 20 rpm or more, and is preferably 2000 rpm or less, more preferably 1500 rpm or less, and even more preferably 1000 rpm or less. If the speed is below the above range, mixing will take a long time, which will affect productivity. If the speed is above the above range, fibrillation will proceed excessively, and the resulting mixture sheet may have poor strength and flexibility.

[0127] In the above step (1), the materials may be mixed and then molded into a bulk shape. Specific methods for molding into a bulk shape include extrusion molding, press molding, and the like. In addition, the "bulk shape" does not specify a particular shape, and may be in the form of a single mass, and includes shapes such as rods, sheets, spheres, and cubes.

[0128] Specific examples of the rolling method in the above step (2) include rolling methods using a roll press, a plate press, a calendar roll machine, or the like.

[0129] After the above step (2), a step (3) may be carried out in which a larger load is applied to the obtained rolled sheet to roll it into an even thinner sheet, or the step (3) may be carried out repeatedly. In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (3) is preferably 2 to 10 times, and more preferably 3 to 9 times. Specific rolling methods include, for example, a method in which two or more rolls are rotated and the rolled sheet is passed between them to process it into a thinner sheet.

[0130] It is also preferable to have a step (4) after the step (2) or the step (3) in which the rolled sheet is crushed, then formed into a bulk shape again, and rolled into a sheet. It is also preferable to repeat the step (4). The number of times of the step (4) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0131] In the above step (4), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include a method of folding the sheet, a method of forming it into a rod or thin sheet shape, a method of chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (2) or step (3) into a different shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0132] Furthermore, the step (4) may be followed by the step (3) or may be repeated. Furthermore, uniaxial or biaxial stretching may be performed in the steps (2), (3) and (4).

[0133] In the above steps (2), (3), and (4), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If it is below the above range, the number of times of rolling increases, which takes time and affects productivity. If it is above the above range, fibrillation may proceed excessively, resulting in a composite sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before rolling. The sample before rolling may be a bulk-shaped raw material composition or a sheet-shaped raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling.

[0134] <Electrochemical devices> The present disclosure also relates to an electrochemical device using the mixture sheet for electrochemical devices of the present disclosure.

[0135] The electrochemical device of the present disclosure may use the mixture sheet for electrochemical devices of the present disclosure as a solid electrolyte mixture sheet, may use it as an electrode mixture sheet, or may use it as a solid electrolyte mixture sheet and an electrode mixture sheet.

[0136] The electrochemical device of the present disclosure preferably comprises a positive electrode, a negative electrode, etc., and more specifically, is preferably a secondary battery comprising these, and is particularly preferably a lithium ion secondary battery.

[0137] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0138] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0139] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0140] The positive electrode may be manufactured by a conventional method, for example, a method in which an electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0141] The density of the positive electrode mixture sheet is preferably 2.50 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3 The range is as follows. If the electrolyte content exceeds this range, the ratio of electrolyte to active material will be low, hindering ion conduction to the active material, and the charge / discharge characteristics at high current density will decrease, making it impossible to obtain high output. If the electrolyte content falls below this range, the active material will be insufficient, and the battery capacity may be poor.

[0142] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less, on one side of the current collector.

[0143] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0144] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0145] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0146] The density of the negative electrode mixture is preferably 1.0 g / cm 3 More preferably, 1.2 g / cm 3 More preferably, it is 2.5 g / cm 3 Less than or equal to 2.2 g / cm 3If the electrolyte content exceeds this range, the ratio of electrolyte to active material will be low, hindering ion conduction to the active material, and the charge / discharge characteristics at high current density will decrease, making it impossible to obtain high output. If the electrolyte content falls below this range, the battery capacity may be poor due to a lack of active material.

[0147] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the mixture layer minus the thickness of the metal foil of the current collector is, as a lower limit, preferably 10 μm or more, more preferably 20 μm or more, and also preferably 500 μm or less, more preferably 450 μm or less on one side of the current collector.

[0148] The secondary battery is preferably a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0149] The secondary battery may have any shape, such as a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the mixture sheet can be changed according to the shape of each battery.

[0150] The solid secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based all-solid secondary battery.

[0151] The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0152] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0153] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0154] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0155] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0156] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0157] (Example) A PTFE powder was obtained by changing the fluorine-containing surfactant to ammonium perfluoroether carboxylate with reference to Preparation Example 2 of WO 2015 / 080291. The standard specific gravity of the obtained PTFE was 2.160. Standard specific gravity (SSG) was determined by the water displacement method according to ASTM D 792 using samples formed according to ASTM D 4895.

[0158] (Synthesis Example 1: Synthesis of Compound 1-1) In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 10 g of fluoropolyether both-terminal alcohol (manufactured by Solvay, Fomblin D2, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was set to 65 ° C, and 5.5 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 20.4 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The volatile matter was removed from the treated solution from which magnesium sulfate had been removed by filtration, and the solution was further dried at 100 ° C for 3 h to obtain the following compound 1-1 (PFPE-PEG). Compound 1-1 was a liquid at 25°C. Compound 1-1: CH3O(CH2CH2O) x1 CH2CF2(OCF2CF2) y (OCF2) z OCF2CH2O(CH2CH2O) x2 CH3 (x1:4, y: average 12.3, z: average 10.2, x2:4, (CH2CH2O) x1 Number average molecular weight: 176, (CH2CH2O) x2 Number average molecular weight: 176)

[0159] 1. Preparation of Solid Electrolyte Mixture Sheet A binder (PTFE), a sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5), and optionally a fluoropolyether (PFPE) were added to a cylindrical container and mixed and granulated by rotating on a rotating stand. Here, by changing the amount of PFPE added, a plurality of solid electrolyte mixtures (compositions) with different volume ratios of PFPE in the mixture were obtained. The obtained solid electrolyte mixture was molded into a bulk shape, and then rolled to a thickness of about 100 μm to obtain a solid electrolyte sheet (Examples 1 and 2). The amount of PFPE added in each solid electrolyte mixture is as shown in Table 1 below. In addition, PFPE has a chemical structure represented by the following formula (I) (m / n is 1.2, number average molecular weight is 5120, and terminal R is CF3 and CF2CF3 in an average ratio of 1:0.17), and is liquid at 25 ° C.

[0160] [ka]

[0161] Solid electrolyte mixture sheets were produced in the same manner as in Examples 1 and 2, except that Compound 1-1 synthesized in Synthesis Example 1 was used instead of PFPE (Examples 3 and 4).

[0162] Solid electrolyte mixture sheets were prepared in the same manner as in Examples 3 and 4, except that LiTFSI (Kishida Chemical Co., Ltd.) was added to compound 1-1 so that the salt concentration became 5 mass % (Examples 5 and 6).

[0163] A solid electrolyte mixture sheet was produced in the same manner as in Examples 1 and 2, except that PFPE was not used (Comparative Examples 1 and 2).

[0164] 2. Preparation of Positive Electrode Mixture Binder (PTFE), conductive additive (VGCF), sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5), and positive electrode active material (LiNi 0.80 Co 0.15 Mn 0.05O2) and optionally fluoropolyether (PFPE) were added to a cylindrical container and mixed and granulated by rotating on a rotating stand. Here, by changing the amount of PFPE added, a plurality of positive electrode mixtures (compositions) with different volume ratios of PFPE in the mixture were obtained. The obtained positive electrode mixture was molded into a bulk shape and then rolled to a thickness of about 100 μm to obtain a positive electrode mixture sheet (Examples 7 and 8). The amount of PFPE added to each positive electrode mixture is as shown in the following Table 2. The PFPE used was the same as that used in Examples 1 and 2.

[0165] A positive electrode mixture sheet was produced in the same manner as in Examples 7 and 8, except that the compound 1-1 synthesized in Synthesis Example 1 was used instead of PFPE (Examples 9 and 10).

[0166] Positive electrode mixture sheets were prepared in the same manner as in Examples 9 and 10, except that LiTFSI (Kishida Chemical Co., Ltd.) was added to compound 1-1 so that the salt concentration became 5 mass % (Examples 11 and 12).

[0167] A positive electrode mixture sheet was produced in the same manner as in Examples 7 and 8, except that PFPE was not used (Comparative Examples 3 and 4).

[0168] 3. Preparation of Negative Electrode Mixture A binder (PVdF), a conductive additive (VGCF), a sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5), and an anode active material (Si) were added to an organic solvent and kneaded using an ultrasonic homogenizer to obtain an anode mixture slurry. The obtained anode mixture slurry was dried to obtain an anode mixture.

[0169] 4. Preparation of Solid Electrolyte Mixture Evaluation Cell The solid electrolyte mixture sheet was punched out to a diameter of 11.28 mm to obtain an evaluation sample. The thickness of the obtained evaluation sample was measured using a micrometer, and then the evaluation sample was sandwiched between carbon-coated thick foils, and current was collected on both sides with SUS electrodes to produce a solid electrolyte mixture evaluation cell.

[0170] 5. Evaluation of solid electrolyte mixture The resistance was measured by an AC impedance method using the solid electrolyte mixture evaluation cell prepared as described above. From the obtained Nyquist plot, the resistance value at the real axis intercept of 300 kHz was read, and the ionic conductivity was calculated from this and the thickness of the electrolyte layer.

[0171] 6. Battery Preparation The solid electrolyte sheet was placed in a cylinder with a diameter of 11.28 mm and subjected to a pressure of 10 kN / cm 2 The solid electrolyte layer was produced by molding at a pressure of 10 kN / cm. The negative electrode mixture was placed on one side of the produced solid electrolyte layer. 2 The electrode was molded under a pressure of 100 MPa. A positive electrode mixture sheet punched to Φ11.28 mm was placed on the opposite side to the negative electrode mixture. An Al foil punched to Φ11.28 mm was placed on the positive electrode side, and a Cu foil punched to Φ11.28 mm was placed on the negative electrode side, and restrained at 5 MPa to obtain an electrode body having a configuration of Al foil / positive electrode mixture layer / solid electrolyte layer / negative electrode mixture layer / Cu foil. Current extraction tabs were attached to the Al foil and Cu foil of the electrode body, respectively, to prepare a battery for evaluation.

[0172] 7. Battery Resistance Evaluation The resistance of the evaluation battery prepared as described above was measured. Specifically, the resistance value of the real axis intercept on the low frequency side of the circular component was read from the Nyquist plot obtained by the AC impedance method, and this was determined as the resistance of the battery.

[0173] 8. Evaluation Results The results of Comparative Examples 1 and 2 and Examples 1 to 6 are shown in the following Table 1. The evaluation results of ionic conductivity are shown relative to the ionic conductivity in Comparative Example 1 as the standard (100).

[0174] [Table 1]

[0175] The results shown in Table 1 suggest the following: (1) The ionic conductivity of Examples 1, 3, and 5 was higher than that of Comparative Example 1, and the ionic conductivity of Examples 2, 4, and 6 was higher than that of Comparative Example 2. This is believed to be because the lubricating effect of the fluoropolyether improved the filling of the solid electrolyte mixture, thereby improving the ionic conductivity. (2) The ionic conductivity of Example 5 was higher than that of Example 3, and that of Example 6 was higher than that of Example 4. This is believed to be because compound 1-1 can dissolve lithium salts.

[0176] The results of Comparative Examples 3 and 4 and Examples 7 to 12 are shown in Table 2 below. Note that the configurations and manufacturing conditions of the electrolyte layer and negative electrode are common to the Examples and Comparative Examples, and therefore are omitted from Table 2. In addition, the evaluation results of the battery resistance are shown relative to the resistance value in Comparative Example 3 as the reference (100).

[0177] [Table 2]

[0178] The results shown in Table 2 suggest the following: (1) The battery resistance of Examples 7, 9, and 11 was smaller than that of Comparative Example 3, and that of Examples 8, 10, and 12 was smaller than that of Comparative Example 4. This is believed to be because the lubricating effect of the fluoropolyether increased the fluidity of the mixture when forming the positive electrode, resulting in an active material layer with a high filling rate, which reduced the battery resistance. (2) The battery resistance of Example 11 was smaller than that of Example 9, and that of Example 12 was smaller than that of Example 10. This is because compound 1-1 can dissolve lithium salts.

[0179] In the above embodiment, the fluoropolyether having a specific chemical structure is exemplified, but the chemical structure of the fluoropolyether is not limited to this.Furthermore, in the above embodiment, the case where the fluoropolyether is contained in the positive electrode side is exemplified, but the same effect can be expected even when the fluoropolyether is contained in the negative electrode side or in the electrolyte layer.In addition, the mixture composition of the positive electrode, the electrolyte layer and the negative electrode is not limited to the above.

[0180] As described above, the composition having the following configuration can reduce the resistance of an electrochemical device having a sulfide solid electrolyte. Contains sulfide solid electrolyte, fluoropolyether and fibrillar resin.

Claims

1. A composition comprising a sulfide solid electrolyte, a fluoropolyether and a fibrillating resin.

2. The composition according to claim 1, wherein the fluoropolyether is at least one of the fluoropolyethers represented by the following formulas (1) to (4): (1) R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2) R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3) R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 Each oxyalkylene unit is independently —CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (wherein, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

3. The Ra 1 ~Ra 3 The composition according to claim 2, wherein each of the groups is independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH 2 CH 2 O)r-(CH 2 CH(CH 3 )O)s-(CH 2 CH(CH 2 CH 3 )O)t-(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently an integer of 0 or 1 or more, and r+s+t+u is 4 to 50.)

4. The Ra 1 ~Ra 3 The composition according to claim 2 or 3, wherein the number average molecular weight of is 40 to 4,000.

5. 4. The composition according to claim 2, wherein each Rf is independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer from 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e and f is 1 or more.

6. The composition according to claim 2 or 3, wherein each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

7. The R 1 ~R 3 The composition according to claim 2 or 3, wherein each of the is independently a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group.

8. 3. The composition according to claim 1, wherein the fibrillar resin is polytetrafluoroethylene.

9. The composition of claim 1 or 2, wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

10. The composition according to claim 1 or 2, wherein the content of the polyalkylene oxide represented by the following formula (6) is less than 20 mass %: (6)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is 0 or an integer from 1 to 2; R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

11. 3. The composition according to claim 1, wherein the content of the lithium salt relative to the fluoropolyether is 0.1 to 30% by mass.

12. A mixture for electrochemical devices, comprising the composition according to claim 1 or 2.

13. The mixture for electrochemical devices according to claim 12, further comprising a conductive assistant.

14. A mixture sheet for electrochemical devices, comprising the mixture for electrochemical devices according to claim 12.

15. An electrochemical device using the mixture sheet for electrochemical devices according to claim 14.

16. (1) mixing a fluoropolyether, a fibrillar resin, and a sulfide solid electrolyte; and (2) rolling the composition obtained in the step (1) into a sheet.

17. The fluoropolyether is at least one of the following formulas (1) to (4): The method according to claim 16, wherein the fibrillary resin is polytetrafluoroethylene. (1) R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2) R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3) R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 each independently represents a group containing a fluorine-free alkylene unit and / or a fluorine-free oxyalkylene unit, Ra 1 ~Ra 3 Each oxyalkylene unit is independently —CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (wherein, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Each Rf is independently a group represented by the following formula (Rf-II) or (Rf-I-II). Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

Citation Information

Patent Citations

  • Non-dehumidifying porous membrane

    JP2012522882A

  • Solid electrolyte slurry, method for manufacturing solid electrolyte sheet, solid electrolyte slurry inclusion body, electrode slurry, method for manufacturing electrode sheet, electrode slurry inclusion body, and method for manufacturing all-solid type lithium ion battery

    JP2016062709A

  • Hybrid composite electrolytes containing fluoropolymers

    JP2022545957A

  • Solid electrolyte composition, solid electrolyte-containing sheet, all-solid-state secondary battery, method for producing solid electrolyte-containing sheet, and method for producing all-solid-state secondary battery

    WO2019087752A1

  • Solid electrolyte composition

    JP2022506854A